Students’ Perceptions Toward Business Mandarin (Study Program of Mandarin for Business and Professional Communication) - Rahman, Sri Khaerani; Fatmawati, Fatmawati; Pasang, Kezia Yansen (Universitas Negeri Semarang, 2025)
Mandarin is the most widely spoken language in the world. Besides that, learning Mandarin in the business field also opens up wider business opportunities, improves communication effectiveness, increases self-confidence, improves negotiation skills, and improves social interaction. The purpose of this study is to identify student perceptions of the importance of Mandarin in the business world. The population in this study were all first, second, and third year undergraduate students of applied Mandarin for Business and Professional Communication at Bosowa University, totaling 15 people. Researchers used the theory of perception and data collection techniques using in-depth interviews. Researchers used a descriptive method with a qualitative approach as a method in this study. After analyzing the data, the researcher found many students' positive perceptions about learning Mandarin in the business sector, where they acknowledged the relatively rapid expansion of Chinese companies, especially in the industrial and franchising fields. This shows that Mandarin can be well received by students. But there are also some students who still don't understand what business examples will be applied in the future. In conclusion, this study emphasizes the importance of learning Mandarin especially in the business sector. In addition, this research is also a reference for writers in improving Mandarin, especially in the business world to meet the needs and expectations of students in the Mandarin Study Program for Business and Professional Communication, Bosowa University.